2023
DOI: 10.3390/educsci13040392
|View full text |Cite
|
Sign up to set email alerts
|

A STEAM Experience in the Mathematics Classroom: The Role of a Science Cartoon

Abstract: A multidisciplinary team collaborated on the development of a learning experience involving 10th grade students using a Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach. The experience was based on the development (conception, implementation, and evaluation) of a science cartoon that aimed to highlight different scientific and technological dimensions related to the diversity of marine worms (Phylo Annelida, class Polychaeta) present in the continental shelf off the coast of Aveiro, Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Engaging pedagogical approaches, particularly those encompassed within STEAM education, are closely related to heightened student interest in STEM subjects. Research has shown that the use of science cartoons can stimulate a STEAM approach and promote learning in 10th-grade students [23]. The use of drones as a pedagogical technology has also been found to have a positive impact on engagement and meaningful learning in STEAM subjects [24].…”
Section: Student Interest In Stem Subjectsmentioning
confidence: 99%
“…Engaging pedagogical approaches, particularly those encompassed within STEAM education, are closely related to heightened student interest in STEM subjects. Research has shown that the use of science cartoons can stimulate a STEAM approach and promote learning in 10th-grade students [23]. The use of drones as a pedagogical technology has also been found to have a positive impact on engagement and meaningful learning in STEAM subjects [24].…”
Section: Student Interest In Stem Subjectsmentioning
confidence: 99%
“…In this context, it is important to strength the pedagogical practices of natural science teachers by incorporating STEAM education within the classroom [36][37][38]. Likewise, the integral curricular composition of STEAM does not limit to the use of technological instruments, dismissing other significant dimensions of science didactics [2,27,39].…”
Section: Introductionmentioning
confidence: 99%